(untitled) (DAPesquisa, 2020)
Observing Erwin Panofsky’s (1955) indications about the way to interpret a work of art, this article proposes an approximation between A pintura em pânico (1943) photomontages book, composed by poet Jorge de Lima (1893-1953), and the postmodernity’s concept developed by Gianni Vattimo in The transparent society (1989). To this end, the avant-garde photomontage is understood as a subversion of the photographic principle itself considered as analogue to reality, and also as a rupture to painting as a pictorial composition’s canonic method. We also resort to the Gianni Vattimo’s established approximation between the concepts of shock in Walter Benjamin (1955) and Martin Heidegger’s stoss (1977), in order to suggest photomontage transcended its period and works as analogue to post modern’s condition, which is, above all, multiform.